(untitled) (The Agriculturists, 2014)
Bangladesh has been divided into 30 Agro ecological Regions (AEZ). Agricultural research, and technology generation and transfer activities have been carried out on this basis. In context of the lack of enough information on different forms of potassium in the soils of the 30 AEZ, an attempt was made to study different forms of potassium of important soils of Bangladesh. As a part of this attempt, an experiment with ten soil samples representing nine different soil series (two of Gopalpur series and one each of Sara, Ishurdi, Ghior, Batra, Sukdebpur, Kumarkhali, Pakuria and Mehendigonj) of the AEZ-12, Low Ganges River Floodplain, was carried out in the Laboratory of the Department of soil science, Bangladesh Agricultural University, Mymensingh to find out the different forms of potassium. The highest value of water soluble potassium (0.08 cmol (+) K g-1) was obtained in Mehendiganj soil series and the lowest value (0.05 cmol (+) K g-1) was obtained in Gopalpur-1, 2 and Ishurdi soil series. The highest amount of exchangeable K (0.29 cmol (+) K g-1) was found in Batra soil series while the lowest (0.13 cmol (+) K g-1) in Gopalpur-1 soil series. The highest amount of available K (0.35 cmol (+) K g-1) was found in both Batra and Mehendiganj soil series while the lowest (0.18 cmol (+) K g-1) in Gopalpur-1 soil series. Considering 0.12 cmol (+) K g-1 as critical limit (BARC, 2012), all soils had available K above the critical level. The highest amount of non-exchangeable K (4.05cmol (+) K g-1) was found in Ghior soil series, while the lowest (2.52 cmol (+) K g-1) was in Mehendiganj soil series. DOI: http://dx.doi.org/10.3329/agric.v12i1.19869 The Agriculturists 2014; 12(1) 140-147